SIMULATION-BASED STUDY OF VOID-CONTROLLED PRECAST SQUARE CONCRETE-FILLED STEEL TUBE COLUMNS UNDER AXIAL COMPRESSION - Jamshad Alam; Nouman Alam (Spectrum of Engineering Sciences, 2025)
This research explores the axial compressive performance of void-controlled precast square CFST columns via experimental testing and finite element analysis (FEA). Conventional CFST columns are plagued by interfacial defects and voids, undermining structural performance. This work suggests a new concept by introducing controlled voids into precast square CFST columns with high-performance self-compacting grout to improve load-carrying capacity and material efficiency. A confirmed finite element model, designed by applying ABAQUS/Standard 2024, perfectly mimics nonlinear interaction among steel confinement, concrete crushing, and grout expansion, with the outcomes reflecting less than 5% deviation from experiments. Parametric studies demonstrate that a 20 mm reserved gap filled with C40 grout enhances ultimate bearing capacity by 4.55% compared to solid columns and lessens structural weight up to 30%. The research shows that up to 20% void ratios maintain more than 95% of the solid column capacity, with grout expansion (0.02–0.05% strain) reducing interfacial debonding. A new load-capacity equation that considers void reduction factors and grout confinement effects is introduced, providing an easy-to-use design tool for engineers. The research shows the possibility of void-controlled precast CFST columns as an efficient and environmentally friendly solution for future construction that weighs performance, constructability, and cost savings. Cyclic/seismic performance and long-term durability are potential future directions of research.